2019
DOI: 10.1016/j.ejvs.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Ten Year Experience of Using Cryopreserved Arterial Allografts for Distal Bypass in Critical Limb Ischaemia

Abstract: WHAT THIS STUDY ADDS Recent long-term results of arterial allografts used for distal bypasses in the setting of chronic ischaemia are lacking. This study confirms that the use of modern cryopreserved arterial allografts allows for an excellent limb salvage rate, at the cost of a relatively high re-intervention rate. This material should be considered as a valuable alternative to prosthetic material when no venous material is available. Objective/Background: In critical limb ischaemia (CLI), current guidelines … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 36 publications
(36 reference statements)
0
9
0
1
Order By: Relevance
“…We have to take into consideration that the use of cryopreserved arteries was indicated in challenging situations concerning critical ischemia and native or prosthetic vascular infection, which are associated with an important risk of amputation, morbidity and mortality. Several studies have reported similar outcomes (13,42), with an emphasis on the dissociation between distal bypass patency and medium to long-term limb and patient survival. This is especially significant, as some authors report that only 45% of patients with critical limb ischemia will remain alive and with both legs 1 year after the diagnosis (43).…”
Section: Discussionmentioning
confidence: 97%
“…We have to take into consideration that the use of cryopreserved arteries was indicated in challenging situations concerning critical ischemia and native or prosthetic vascular infection, which are associated with an important risk of amputation, morbidity and mortality. Several studies have reported similar outcomes (13,42), with an emphasis on the dissociation between distal bypass patency and medium to long-term limb and patient survival. This is especially significant, as some authors report that only 45% of patients with critical limb ischemia will remain alive and with both legs 1 year after the diagnosis (43).…”
Section: Discussionmentioning
confidence: 97%
“…For patients requiring revascularization surgery, unavailability of autologous bypass grafts may lead to loss of an opportunity for appropriate therapy and consequent poor prognosis. Although cryopreserved arterial allografts can be a surrogate for autologous small-caliber grafts with acceptable long-term patency, the availability is rather limited because of the shortage of donors and insufficient operation of organ / tissue banks to preserve and provide allografts [16][17][18]. The present study was designed to address this healthcare problem through validating the feasibility of xenogeneic implantation of HHP-decellularized vascular grafts using bovine arterial grafts and a porcine carotid arterial interpose model.…”
Section: Discussionmentioning
confidence: 99%
“…По данным S. Masmejan et al [13], хорошие результаты возможны при реконструкции артерий нижних конечностей криоконсервированными аллографтами с отсутствующей аутовеной у 38 пациентов. Из 42 шунтов проксимальный анастомоз был выполнен в бедренную артерию в 41 случае (98%), дистальный анастомоз был выполнен в 21 случае (50%) в большеберцовые артерии, в тибиоперинеальный ствол -в девяти случаях (21%) и в дистальную подколенную артерию в 12 случаях (28%).…”
Section: Discussionunclassified